Comparison of ZETA Fast (PTS) (Optopol Technology) and Humphrey SITA Fast (SFA) (Carl Zeiss Meditec) Perimetric Strategies - Basil Mathews; Jeff Laux; Cassandra Barnhart; David Fleischman (Journal of Ophthalmology)
Purpose. To compare two threshold strategies for visual field assessment, ZETA Fast (Optopol Technology) and Humphrey SITA Fast (Carl Zeiss Meditec), in controls and subjects with glaucoma. Patients and Methods. A prospective case-control study was carried out in which the clinical practice study included 26 controls and 26 glaucoma subjects. Testing for each strategy was monocular. Quantitative comparisons of mean deviation (MD), pattern standard deviation (PSD), visual field index (VFI), and test duration were made using two one-sided t-tests and Wilcoxon signed-rank tests. Confusion matrices were constructed to assess Optopol’s detection as a proxy for Zeiss’s detection of early glaucomatous defects. Receiver operating characteristic (ROC) curves were used to assess MD and PSD’s discriminability. Results. The difference in MD values (Optopol-Zeiss) was within the margin for controls (difference = 0.36, p=0.06), but not for glaucomatous subjects (difference = 2.16, p=1.0). The Optopol strategy took longer than the Zeiss strategy in both controls (difference = 23 seconds, p=0.001) and glaucomatous subjects (difference = 49 seconds, p<0.001). PSD values were higher and VFI values were lower from Optopol in glaucomatous subjects (p<0.001 and p=0.002). Optopol was 92% sensitive in capturing early glaucomatous defects with MD <−2 when compared to Zeiss (p<0.001). ROC analysis shows Optopol yields higher discriminability than Zeiss for MD/PSD indices. Conclusions. Both strategies enable effective identification of glaucomatous defects within 6 minutes; they also offer high sensitivity with a high correlation in global indices between the two strategies. The Optopol strategy is an alternative to the Zeiss counterpart with the limitation of a marginally longer testing protocol but a higher sensitivity of detecting glaucomatous defects.